Shoulder injuries in competitive swimmers in KwaZulu- - Puckree, T; Thomas, KJ (South African Journal of Sports Medicine, 2006)
Objective. To determine the incidence of shoulder injuries in competitive swimmers in KwaZulu-Natal, a province in South Africa. Design. A cross-sectional survey was conducted. A random sample of 96 swimmers from a pool of 300 swimmers registered with first-division clubs affiliated to the KwaZulu-Natal Aquatics Association participated in the study by informed voluntary consent. Data were gathered using a validated questionnaire. Setting. Data were gathered at time trials, races and club meetings. Main measures. Variables monitored included the incidence of shoulder injuries, shoulder pain and proportion of overuse injury. Results. Seventy-one per cent of the swimmers had shoulder pain and 64% reported injury to the shoulder. Forty-six per cent of the swimmers with pain complained of anterior shoulder pain, while 65% of all injuries were due to overuse. The commonest diagnoses included tendonitis (35%), muscle imbalance (29%), impingement (19%) and other (17%). Sixty-nine per cent of the swimmers swam freestyle which was related to 70% of the injuries. Eighty-one per cent of the injured swimmers sought physiotherapy for the shoulder pain. Conclusion. The incidence of shoulder injuries in competitive swimmers is high. This study shows the need for more research into swimming injuries, and the conditioning and rehabilitation of athletes in South Africa. South African Journal of Sports Medicine Vol. 18 (1) 2006: pp. 10-12